Evaluation Of Medicine Purchasing Methods At Metro Sidoarjo Hospital, Mother And Child Hospital, In Terms Of Efficiency And Medicine Availability - Wizurai Hakim; Asri Asri; Mochamad Mochklas (Jurnal Manajemen Kesehatan Yayasan RS.Dr. Soetomo, 2026)
Drug procurement at the Mother and Child Hospital plays a strategic role in ensuring operational efficiency and the availability of essential drugs for maternal and neonatal services. This study aims to evaluate the drug procurement methods at Mother and Child Hospital Metro Hospitals Sidoarjo using internal data from 2020 to 2024, focusing on tender mechanisms, direct procurement, consignment, and procurement based on usage history. The study used a quantitative descriptive method with an ABC-VEN analysis approach, as well as measuring efficiency indicators (cost per unit of medicine and waste rate) and medicine availability (percentage of stock-outs <5%). The results showed that the tender method provided the highest level of efficiency with cost savings of 25% and drug availability reaching 98%, while procurement based on usage history was able to reduce excess stock by up to 15%. Based on these findings, it is recommended that historical drug usage data be integrated as a basis for procurement decision-making to improve efficiency and availability. This study is expected to contribute to the development of pharmaceutical management in maternity hospitals in Indonesia and to provide input for the formulation of national policies and regulations related to drug procurement.